Basic psychological needs and organizational stress among student-athletes in Nigeria (2022)
Organizational stress poses a lot of threat on student-athletes unique population and causes numerous undesirable consequences, which affect their well-being, academic, personal life and sport performance. The aim of this study was to examine the influence of basic psychological needs on organisational stress among student- athletes in Nigeria. This study employed correlational descriptive research design. The participants were 200 student-athletes that participated in 2022 NUGA held in Lagos, Nigeria. Convenient sampling method was used to select the sample size. The participants completed Basic Need Satisfaction in Sport Scale (BNSSS) and the Organizational Stressor Indicator for Sport Performers (OSI-SP) to collect data. Data analysis was conducted using Pearson Product Moment Correlation (PPMC) and multiple regression analysis. The results of the study showed that there was significant positive correlation between autonomy and organisational stress (r=0.181, p<0.05); relatedness and organisational stress (r=O.204, p<0.05), Regression analysis showed that joint contributions of basic psychological needs accounted for about 53% of variance influencing dependent variable. Relatedness was only found to have relative significant contribution on organisational stress. It can therefore be concluded that fulfilling and satisfying the basic psychological needs of student-athletes can reduce organisational stress and enhance performance and over all well-being